Microbial Profile and Antibiotic Sensitivity in Duodenal Ulcer Perforation Peritonitis: Empirical vs. Culture-Guided Therapy—A Prospective Observational Study in Eastern Nepal - Khadga, Ajit; Mandal, Manish Kumar; Shah, Sachidanand; Shrestha, Dipesh; Khadga, Sujita (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Perforation peritonitis (PP) due to duodenal ulcer perforation (DUP) remains a major surgical challenge associated with considerable postoperative morbidity and mortality. Although empirical broad-spectrum antibiotics are routinely administered, their efficacy varies with evolving local resistance patterns. This prospective interventional study aimed to determine the bacteriological profile and antibiotic sensitivity pattern from intraoperative peritoneal fluid and to compare postoperative outcomes between patients receiving empirical versus culture-guided antibiotic therapy.METHODS Fifty patients with DUP-induced PP who underwent emergency laparotomy at Nobel Medical College Teaching Hospital, Eastern Nepal (November 2019–October 2020), were included. Peritoneal fluid was collected intraoperatively for culture and sensitivity testing. Patients were allocated into Group I (empirical antibiotics, n = 28) and Group II (culture-guided antibiotics, n = 22). Postoperative complications, secondary procedures, mortality, and duration of hospital stay were compared between groups.RESULTS The mean age was 47.7 ± 13.6 years; 82% were male. The mean hospital stay was 7.82 ± 4.49 days. Positive culture growth occurred in 44% of samples, most commonly Escherichia coli (28%) and Klebsiella pneumoniae (6%). The highest antibiotic sensitivity was observed to Cefotaxime (65%) and Levofloxacin (50%). Patients receiving culture-guided therapy had a lower postoperative complication rate (13.7%) than those on empirical therapy (32.1%), with improved clinical recovery and shorter hospitalization. Associations of alcohol use (p = 0.314) and drug abuse (p = 0.240) with complications were not statistically significant.CONCLUSIONS Culture-guided antibiotic therapy significantly reduces postoperative morbidity and shortens hospital stay in patients with perforation peritonitis compared to empirical therapy. Multicenter studies are warranted to validate these findings.